2020
DOI: 10.1155/2020/8839490
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Anticancer Activity and Untargeted Secondary Metabolite Profiling of Crude Bacterial Endophyte Extracts from Crinum macowanii Baker Leaves

Abstract: This study isolated and identified endophytic bacteria from the leaves of Crinum macowanii and investigated the potential of the bacterial endophyte extracts as antibacterial and anticancer agents and their subsequent secondary metabolites. Ethyl acetate extracts from the endophytes and the leaves (methanol: dichloromethane (1 : 1)) were used for antibacterial activity against selected pathogenic bacterial strains by using the broth microdilution method. The anticancer activity against the U87MG glioblastoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 117 publications
0
19
1
1
Order By: Relevance
“…Bacillus species are known to produce bioactive metabolites with antitumor and antibacterial species ( Shao et al, 2021 ). Sebola et al (2020) , conducted a study to evaluate the antitumor activity of crude extracts from the medicinal plant Crinum macowanii Baker, and the results showed that the crude extracts of B. safensis had growth inhibition of 50% against A549 cells at a concentration of 100 μg/ml. Ramasubburayan et al (2015) , conducted a similar study in which the anticancer activity of the crude extract of B. subtilis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus species are known to produce bioactive metabolites with antitumor and antibacterial species ( Shao et al, 2021 ). Sebola et al (2020) , conducted a study to evaluate the antitumor activity of crude extracts from the medicinal plant Crinum macowanii Baker, and the results showed that the crude extracts of B. safensis had growth inhibition of 50% against A549 cells at a concentration of 100 μg/ml. Ramasubburayan et al (2015) , conducted a similar study in which the anticancer activity of the crude extract of B. subtilis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic bacteria and fungi have been isolated from many plant species, but only a few Amaryllidaceae plants have been studied thus far. The plants that have been investigated are Narcissus tazetta [ 25 ], Crinum macowanii [ 30 , 31 , 32 ] and Lycoris radiata [ 33 ]. The latest example was reported by Spina et al [ 26 ], with in vitro bulblets of L. aestivum .…”
Section: Discussionmentioning
confidence: 99%
“…When going deeper in detail and when focusing on different plant tissues, we could highlight similarities but also some interesting differences. The leaf endophytic bacteria, Arthrobacter , Luteibacter and Pseudomonas , were common to other Amaryllidaceae plant leaf tissues [ 32 , 33 ]. Concerning roots, Bacillus and Paenibacillus genera were predominant in Leucojum aestivum as well as in Lycoris radiata [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another report, Sebola et al (2020) analyzed the antibacterial (against 11 pathogenic bacteria constituting both Gram-positive and Gram-negative bacteria) and anticancer activity (against glioblastoma and lung carcinoma cell lines) of ethyl acetate extracts of bacterial endophytes ( Bacillus safensis, Pseudomonas cichorii , and Arthrobacter pascens ) isolated from Crinum macowanii (commonly known as Cape coast lily; used to cleanse blood, and treat cough and kidney diseases) leaves. Further, using LC-Q-TOF-MS analysis of crude extracts of the bacterial endophytes revealed the presence of antibacterial and anticancerous compounds such as lycorine, angustine, crinamidine, and powelline.…”
Section: Metabolomics For Investigation Of Endophyte Metabolomementioning
confidence: 99%